Evidence of prolonged disturbances in the haemostatic, hemorheologic and inflammatory profiles in transmural myocardial infarction survivors - Sargento, Luis; Saldanha, Carlota; Monteiro, José; Perdigão, Carlos; eSilva, João Martins (Thrombosis and Haemostasis, 2003)
Haemostatic, hemorheologic and inflammatory disturbances have been associated with acute coronary syndromes. Most knowledge is reported in cross sectional studies and are without time dependent evolution of these profiles.The aim of this study was to evaluate, during the first year, the evolution of the haemostatic, hemorheologic and inflammatory profiles determined at hospital discharge in survivors with transmural myocardial infarction (MI).Eighty eight (79 male; 9 female) mean age of 58 ± 11 years, survivors of a transmural MI were prospectively studied at discharge, 6 months and one year after the event. Haemostatic (protein C, antithrombin III and plasminogen activator inhibitor 1), hemorheologic (blood fluidity and components) and inflammatory profiles (polymorphonuclear elastase and leukocyte count) were determined using standard methodology.The results of the study can be summarized as follows: (1) Protein C decreased (p < 0.05) over time while PAI-1 only varied significantly until 6th month. (2) Plasma viscosity and fibrinogen (p < 0.001) decrease over time, while erythrocyte aggregation (p < 0.001) and haematocrit increased. Whole blood viscosity did not vary. (3) Leukocyte decreased (p < 0.001) and elastase did not (4). Those patients with cardiovascular events (n = 7) had higher PAI-1 concentration (p<0.05) and leukocyte count (p < 0.01), at discharge (5) Left ventricle ejection fraction correlated significantly with plasma viscosity (r = 0.35 p < 0.05). The results of this longitudinal study show dynamic modifications of the haemostatic, hemorheologic and inflammatory profiles during the first year of a transmural myocardial infarction. In addition, there are interrelations between them and the clinical profile that could help to explain the clinical evolution of this group of patients.
Keywords: Myocardial infarction; protein C; elastase; plasminogen inhibitor 1 and erythrocyte aggregation; longitudinal study